(untitled) (American Journal of Management, 2023)
This study surveyed 632 business and public education mid-level managers to ascertain both the importance of and their confidence in using six research-based management competencies. Both groups rated the six as equally or highly valuable; however, educational managers valued conflict resolution more than business counterparts. The education group reported less confidence using their skills in problem solving, conflict resolution, and strategic planning. While both groups perceived most of the six competencies as equally valuable, the two groups did not feel similarly confident using the skills. Participants’ ratings of skill-importance did not predict their level of confidence using the skills.